KETERHUBUNGAN DAN BATASAN ANTARA PERPUSTAKAAN, MASYARAKAT INFORMASI DAN DEMOKRASI: SEBUAH STUDI RINTISAN - Purwanto Putra; Renti Oktaria (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
This research was aimed to examine and tries to see the interrelationships and boundaries between the three components of library, information society and democracy in a pilot study. The study of the relationship of democracy as well as its boundaries with the information society and libraries will try to fill in the blanks regarding information that can be filled in to